"As gangues não existem mais": formação e práticas de grupos de gangues nos bairros Mapiri e Liberdade em Santarém-PA na década de 1990 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
The fieldwork for this research was carried out in the city of Santarém-PA, in Liberdade and Mapiri neighborhoods, with some people aged between 30 and 35 years old, ex-members of organized groups known as "gangs", who worked in these neighborhoods in the 1990s of the twentieth century. The guiding question of the research was: how did these subjects carried out participation in deviant groups despite the constraints of external controls? From field work and observation, it was possible to make a review of their practices - in the 1990s, the time of the rise of gangs - in addition to obtaining questions and answers about how they were constituted as gangs and what are their mechanisms of territorial division and control. And to compose the analysis, I used the period’s newspapers to understand the categories given to these people (and their organizations) by the institutions and another groups.
Keywords: Gangues; Desvio comportamental; Censura e controle; Reação social; CNPQ:: CIÊNCIAS HUMANAS